Successful treatment of limited-stage small-cell lung cancer in the right mainstem bronchus by a combination of chemotherapy and argon plasma coagulation. (2017) - Takeda, Takayuki; Itano, Hideki; Takeuchi, Mayumi; Nishimi, Yurika; Saitoh, Masahiko; Takeda, Sorou
Abstract: The current standard-of-care treatment for patients with limited-stage small-cell lung cancer (SCLC) is concurrent chemoradiotherapy for local and systemic control. However, standard-of-care treatment strategies have not been established for those with limited-stage SCLC who have a history of thoracic radiotherapy due to concerns with complications associated with radiation overdose. A 37-year-old male developed an aspergilloma in the postoperative left thoracic space after he was treated with concurrent chemoradiotherapy for mediastinal type lung adenocarcionoma and subsequent left upper lobectomy for heterochronous dual adenocarcinoma. Fiberoptic bronchoscopy was performed to examine the status of the suspected bronchopleural fistula when a polypoid mass was observed in the right mainstem bronchus. A histological examination showed that the mass was SCLC at a clinical stage of cTisN0M0, stageIA, without local invasion. Since thoracic radiotherapy was not an option due to a previous history of thoracic irradiation, a combination treatment of carboplatin and etoposide was administered for 4 cycles and resulted in good partial response. In addition, argon plasma coagulation (APC) was performed as an alternative to curative radiotherapy on day 22 of the 4th cycle. The 5th cycle was administered 7 days after APC at which the anticancer therapy was completed. The patient remains disease-free 60 months after the completion of treatment, which suggests that this combination therapy may resolve very early-stage SCLC.